Preparation of reduced Ni-Nb-O composite hydrogenation catalysts for highly selective conversion of free fatty acids to n-alkanes. (15th December 2020) - Chen, Lei; Li, Guangci; Zhang, Mingjie; Wang, Da; Li, Shuangju; Zhang, Chuanhui; Li, Xuebing; Chung, Keng H.
Graphical abstract: Abstract: Catalytic deoxygenation of fatty acids to alkanes is an ideal route to produce biodiesel with high heating value. However, traditional transition-metal sulfide and noble metal catalysts are sulfide-contaminated, high cost, or easily poisoned. To overcome the above issues, this work developed a non-noble and sulfide-free reduced transition-metal composite Nix Nby Oz, which was effective to selectively hydrogenate stearic acid, a typical fatty acid model compound, to diesel-range alkanes. By using a simple slurry method, reduced Nix Nby Oz catalysts have been successfully prepared with an outstanding catalytic performance. The results showed that catalyst Ni0.5 Nb0.5 Oz effectively converted stearic acid to n -alkanes with nearly 100% conversion and >99% n -alkanes selectivity at mild conditions (513 K and 3.5 MPa of H2 pressure). Appropriate Nb species improved the dispersion of Ni species, which may supply more hydrogenation active sites. Two possible reaction routes of stearic acid were proposed, and the hydrogenolysis of stearyl stearate was confirmed as the rate-determining step based on the kinetics experiments. Because of moderate acidity of Nb species, the ratio of C17 /C18 alkane was not markedly affected by reaction conditions when the conversion of stearic acid was higher than 99%. Moreover, catalyst Ni0.5 Nb0.5 Oz showed a high recycle ability and compatibility for other long-chain fatty acids, demonstrating that catalyst Ni0.5 Nb0.5 Oz is a promising green catalyst for producing biodiesel from fatty acids.